To study the effect of early versus late trophic feeding in preterm neonates with mild respiratory distress syndrome - Sinha, Rahul; Venkatnarayan, K; Dalal, Shamsher; John, B M; Syed, V Sabid (Indian Journal of Child Health, 2016)
Background: The respiratory distress syndrome in preterm neonates is mostly due to surfactant deficiency. The incidence and severity of respiratory distress syndrome are related inversely to the gestational age of the newborn infant. The early nutritional support, in these preterm neonates with respiratory distress, prevents complications, and maintains positive energy balance. Objective: The aim was to study the effect of early versus late trophic feeding in preterm neonates with mild respiratory distress syndrome. Materials and Methods: This was a prospective study conducted in babies admitted to neonatal intensive care unit (NICU) from January 2013 to January 2016 in Military Zonal Hospital. A total of 200 babies with a gestational age